GPs' experiences with enhanced collaboration between psychiatry and general practice for children with ADHD. (2nd July 2016) - Hassink-Franke, Lieke J.A.; Janssen, Mijnke M.M.; Oehlen, Guy; van Deurzen, Patricia A.M.; Buitelaar, Jan K.; Wensing, Michel; Lucassen, Peter L.B.J.
Abstract: Background: Most general practitioners (GPs) do not feel comfortable with diagnosing and treating children with attention deficit hyperactivity disorder (ADHD). This is problematic since ADHD is a prevalent disorder and an active role of GPs is desired. In the Netherlands a collaborative ADHD programme was established, comprising of shortened diagnostic assessment in specialized mental healthcare followed by psycho-education in mental healthcare and pharmacological treatment by pre-trained GPs. Objectives: To explore the experiences of GPs regarding the diagnosis and treatment of children with uncomplicated ADHD within this programme. Methods: Semi-structured interviews with 15 GPs were conducted. The GPs participated in an evaluation of the collaborative ADHD programme. Data was analysed using the principles of constant comparative analysis. Results: Most participating GPs expressed reluctance to diagnose ADHD themselves. The reluctance was due to a lack of time, knowledge and experience. The GPs welcomed the collaborative programme because it met their need for both quick and adequate diagnosis by a specialist. Furthermore, an online ADHD course, offered by the programme, gave them the confidence to start and monitor ADHD medication. Finally, they appreciated the possibility of consulting a specialist when necessary. Conclusion: GPs preferred that ADHD was diagnosed by a specialist. In the context of the ADHD collaborative programme, they felt competent and comfortable to start and monitor medication in children with uncomplicated ADHD. Key Messages: Within a collaborative ADHD programme for children, participating GPs were positive about a quick and specialist diagnostic process within secondary care. After an online course, GPs felt confident to start and monitor ADHD medication in children with uncomplicated ADHD. GPs were content about the collaboration between primary and secondary care.